The struggle of preserving self-esteem and professional identity: A grounded theory study of specialists’ experiences serving in the public health system in Rajasthan, India - Anushree Joshi; Jallavi Panchamia; Dileep Mavalankar; Bharati Sharma (PLoS ONE, 2025)
This study aimed to explore and describe the experiences of specialist physicians at rural community health centers (CHCs) and determine the factors accounting for their retention and attrition in Rajasthan, India. Twenty-one medical professionals from different public health facilities in Rajasthan, selected through purposive sampling, were interviewed in depth. Strauss and Corbin’s grounded theory approach was used to develop a theory/model. Open, axial and selective coding were used to identify the major themes/categories and develop the core category of the model. Strauss and Corbin’s paradigm model was employed to establish linkages among the categories structured in terms of conditions, action-interaction strategies and consequences to explore the experiences of specialist physicians. The central theme of the model, ‘The struggle of preserving Self-esteem and Professional identity’, captures the experiences of specialist physicians working at the rural CHCs in Rajasthan’s public healthcare system. The disadvantages of an underdeveloped rural setting, local political climate and various healthcare system factors challenge the specialists’ self-esteem and professional identity culminating in their decision to remain or quit the system. This further leads to their acute shortage in the system which affects the quality and provision of rural healthcare services in the state. The state government and essential stakeholders must collaborate to enact policies addressing specialist physicians’ personal and professional needs, which include improving developmental infrastructure, healthcare system processes, local governance and accountability. Such policy packages can generate sustainable solutions to mitigate the high attrition rate of specialists in rural CHCs and strengthen rural healthcare services in Rajasthan.